2019
DOI: 10.1177/0300060519847345
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori-positivity in the gallbladder and stomach and effect on gallbladder pathologies

Abstract: ObjectiveHelicobacter pylori commonly occurs in the stomach, but localizations outside the stomach and related diseases have also been investigated. However, the relationship between H. pylori and gallstones remains controversial. We aimed to investigate the relationships between H. pylori in the stomach and the gallbladder and gallstones.MethodsThis prospective case-control study included patients who underwent cholecystectomy because of gallstones, pancreatic head cancer, or hepatic resection. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Other factors that can increase the chance of developing cholecystolithiasis, may include, but not limited, to obesity, older age, rapid weight reduction method and fertility. Some studies described the presence of H. pylori in the biliary system is also one the causes of developing gallstones and gallbladder polyps [4], while others showed no relation between the presence of H. pylori in the stomach or in the biliary system to cause any gallstone [5].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that can increase the chance of developing cholecystolithiasis, may include, but not limited, to obesity, older age, rapid weight reduction method and fertility. Some studies described the presence of H. pylori in the biliary system is also one the causes of developing gallstones and gallbladder polyps [4], while others showed no relation between the presence of H. pylori in the stomach or in the biliary system to cause any gallstone [5].…”
Section: Discussionmentioning
confidence: 99%
“…(Sohouli et al, 2020) have confirmed in their study that patients with H. pylori infection can increase risk of cancer such as; lymphoma, pancreas disease and atherosclerosis. (Ari et al, 2019) have shown in their study to isolates H. pylori from cholecystectomy samples found it in 40% of patients without gallstones and 20% of those with gallstones, The previous information revealed that H. pylori infection may worsen serum lipid levels through continuing chronic inflammation (Iwai et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Several factors such as chemical composition, structure, morphology, and microbiological findings have been reported as different mechanisms leading to the formation of gallstones [ 3 , 4 ]. Gallstones form as a result of a settling process in which solid particulates settle to the bottom of a liquid and form a sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) is a spiral, microaerophilic, gram-negative bacterium responsible for this situation [ 4 ]. It lives in the stomach and is related to acute and chronic gastritis, gastric and duodenal ulcer, gastric and pancreatic adenocarcinoma, and lymphoma of gastric mucosa-related lymphoid tissue (MALToma) [ 3 , 11 , 12 ]. The presence of H. pylori outside the stomach and diseases associated to this situation have been investigated [ 3 ]; such as, in primary sclerosing cholangitis and primary biliary cirrhosis, H. pylori DNA was detected in human liver tissue samples [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation